Characterisation of submicron size entrainment in the aqueous product stream of a 40 mm diameter centrifugal extractor for 30% tbp/nitric acid biphasic system. (1st January 2014) - Kumar, Shekhar; Shekhawat, Rajendra Singh; Singh, Abhishek; Balamurugan, M.; Priyadarshini, N.; Sampath, M.; Mudali, U. Kamachi
Annular centrifugal extractor is a favoured solvent extraction contactor where process flowsheet requires a low hold-up, lower residence times and compact layout. However during operation of annular centrifugal extractor, a small entrainment, generally of the order of few hundred ppm, is always observed. To characterise this small entrainment, hydrodynamic experiments in a no-mass transfer mode were conducted on a 40 mm centrifugal extractor with 30%TBP/dodecane and acidified water. The aqueous product stream was analysed by dynamic light scattering based methods and drop size distribution was experimentally measured. The maximum entrained micro-drop size was typically below 1 μm in most of the cases and in the rest it was well below 10 μm. Thus the original assertion, that small entrainment occurred due to micro-sized drops, was proved right. However due to complex relations of peak locations and relative peak intensities to the physical and operating properties of solvent extraction system, mathematical modelling or correlation of experimental results was not feasible.